Propagandes, films et guerre du Vietnam : histoires d’hommes et de femmes ou propagande du « genre » de The Deer Hunter (1978) à Path to War (2002) - Alexandra Boudet-Brugal (Revue LISA)
Drawing from a selection of movies (and a documentary), I propose to study some images of men and women in the context of the Vietnam War, taking a closer look at women’s. To some extent, they contribute to revealing how the “field of battle” has become a “field of gender” and what is at stake. The film as a medium is involved in what we may call “war propaganda”: in the movies, there are elements that are part and parcel of what makes the traditional image of men and women in wartime. It is mostly about defining men as visible acting characters on stage and women as secondary characters (Path to War), playing the part of the apolitical and maternal Other (Heaven and Earth). Indeed, their historical identity mainly defines them as “those who do not make war” (The Deer Hunter). Sometimes, the female image is ambivalent. But the portraits of those who betray their gender, the women warriors (Full Metal Jacket) and the unfaithful (Coming Home), though proposing new facets, do integrate into gender war propaganda. Occasionally the images showed also reveal new voices and paths (Regret to Inform, In Country, Heaven and Earth). It is true that overall we encounter no heroines but “super-hero soldiers” who rescue women (Heaven and Earth, Coming Home); however the representations offer a new space, emancipated from historical and social expectations. But do these stories suggest that women’s stories may be war stories and be part of history?